How does family functioning contribute to academic-related outcomes of Chinese adolescents: the mediating role of spirituality - Shek, Daniel T. L.; Leung, Kim Hung; Li, Xiang; Dou, Diya; Zhu, Xiaoqin (Frontiers in Psychology, 2024)
While family functioning is crucial to adolescent developmental outcomes, the mediating role of spirituality in the relationship between family functioning and academic-related outcomes of adolescents has been sparsely explored, particularly in non-Western contexts. To address this gap, based on a short-term longitudinal study, we examined the influence of family functioning on the academic values and academic anxiety of 4,981 Chinese adolescents in Sichuan, China, with spirituality as the mediator. We gathered data from students aged 11 and above at Wave 1 and at six months later (Wave 2). Analysis utilizing structural equation modelling indicated that prior family functioning positively and negatively predicted subsequent academic values and academic anxiety respectively, with spirituality as a significant mediator. Theoretically, this study helps to build up a conceptual model on how family functioning and spirituality of adolescents shape academic values and academic anxiety of adolescents. Practically, the present findings highlight the significance of enhancing family functioning and adolescent spirituality to help adolescents strive for academic success.